2012
DOI: 10.1080/10668921003677183
|View full text |Cite
|
Sign up to set email alerts
|

Retention Among Community College Student-Athletes

Abstract: This study explored the impact of financial-aid on student-athletes' academic progression from freshmen to sophomore year in associates' degree programs in Oklahoma. Differences were found according to socioeconomic status (SES), gender, and race=ethnicity and between athlete and nonathlete students.Community colleges are a major provider of postsecondary education and job-related training received by students enrolled in institutions of higher education (Bragg, 2001;Cohen & Brawer, 2008). The more than 1,100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…While much research has been conducted with student-athletes at 4-year institutions, the amount of research focusing on student-athletes at community colleges has been far less (Kissinger et al, 2011;Mendoza et al, 2012). As the number of students participating in community college-level athletic programs continues to increase, so too will the need for an educated and informed group of support personnel in place to assist student-athletes manage the increased pressures associated with their dual role in the college system.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…While much research has been conducted with student-athletes at 4-year institutions, the amount of research focusing on student-athletes at community colleges has been far less (Kissinger et al, 2011;Mendoza et al, 2012). As the number of students participating in community college-level athletic programs continues to increase, so too will the need for an educated and informed group of support personnel in place to assist student-athletes manage the increased pressures associated with their dual role in the college system.…”
Section: Resultsmentioning
confidence: 96%
“…Although much is known about the experience of student-athletes at 4-year institutions, relatively little attention has been paid to the experiences of student-athletes at the community college level (Mendoza, Horton, & Mendez, 2012). While non-Division I student-athletes previously were thought to experience different types of stress than Division I student-athletes (Miller & Kerr, 2002), more recent findings suggested that community college student-athletes not only face their own unique set of challenges, but also many of the same issues facing their peers at 4-year institutions (Bush, Castaneda, Hardy, & Katsinas, 2009;Kissinger, Newman, Miller, & Nadler, 2011;Storch & Ohlson, 2009).…”
mentioning
confidence: 99%
“…Students often utilize these institutions to re-tool their skills to re-renter the workforce, participate in activities leading to lifelong learning, and earn credits toward a certificate or degree in their chosen field of study (Bahr, 2013a, 2013b). The literature further suggests that community colleges serve as a path to college athletics for men and women who have a desire to continue their athletic participation after high school (Horton, 2009a; Mendoza, Horton, & Mendez, 2012). Mendoza et al (2012) suggested that “athletic programs often serve as the primary motivation for many individuals to pursue higher education, especially, perspective [ sic ] students from low-income and ethnic minority backgrounds” (p. 202).…”
mentioning
confidence: 99%
“…The literature further suggests that community colleges serve as a path to college athletics for men and women who have a desire to continue their athletic participation after high school (Horton, 2009a; Mendoza, Horton, & Mendez, 2012). Mendoza et al (2012) suggested that “athletic programs often serve as the primary motivation for many individuals to pursue higher education, especially, perspective [ sic ] students from low-income and ethnic minority backgrounds” (p. 202).…”
mentioning
confidence: 99%
“…Community colleges also provide students an opportunity to continue playing competitive sports after high school (Mendoza, Horton, & Mendez, 2012).…”
Section: Characteristics Of Community College Athleticsmentioning
confidence: 99%